A Systematic Review of Key Issues in Public Health - Boccia, Stefania (Springer, 2015)
This wide-ranging study reviews the state of public health worldwide and presents informed recommendations for real-world solutions. Identifying the most urgent challenges in the field, from better understanding the causes of acute diseases and chronic conditions to reducing health inequities, it reports on cost-effective, science-based, ethically sound interventions. Chapters demonstrate bedrock skills essential to developing best practices, including flexible thinking for entrenched problems, conducting health impact assessments, and working with decision-makers. From these current findings come long-term practice and policy goals for preventing disease, promoting health, and improving quality of life, both locally and globally.